PRECAUTIONS TAKEN BY THE GENERAL PUBLIC DURING COVID 19 PANDEMIC ASSOCIATED LOCKDOWN PERIOD IN THE SUBURBS OF CHENNAI CITY - A SURVEY (Cuestiones de Fisioterapia, 2020)
At the beginning of december in 2019, Coronavirus (COVID -19) outbreak had become a major public health issue and self-isolation is among the suggestions to reduce the spread of the infection. A self structured questionnaire was distributed through